Corporate Cash Shortfalls and Financing Decisions - Huang, Rongbing; Ritter, Jay R (Review of Financial Studies, 2021)
Abstract Given their actual revenue and spending, most net equity issuers and an overwhelming majority of net debt issuers would face immediate cash depletion without external financing. Debt issuers tend to have short-lived cash needs, while equity issuers often have persistent cash needs. On average, debt issuers immediately spend almost all of the proceeds, while equity issuers retain much of the proceeds in cash. Anticipated near-future cash needs and fixed costs of financing help explain the fraction of the proceeds being retained. Our findings support a funding-horizon theory in which cash needs and the nature of cash needs motivate financing decisions.